Dreaming Beyond a World on Fire: Radical Imagination as Research Method - Watson, Amanda (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
Beginning in 2021 after two devastating climate events in British Columbia, The Imagine Kin Project sought to take the temperature of young people living in Metro Vancouver who were concerned about climate futures and economic insecurity as they imagined their future relations in this context. This pilot research involved a series of three focus groups and an arts-based workshop. Presenting original data from the focus groups, I argue for the use of radical imagination as a methodological tool to understand people’s experiences of intersecting precarity, invite reflection on and validation of related anxieties, and foster the conditions for radical hope among participants. Further, I suggest that questions of kinship and critical caring relations are useful prompts for radical imagination as these personal subjects allow insights into intersectional precarity to be collectively politicized in perhaps less intimidating ways than would more direct questions about social movements. Findings from this research show that imagining the future through collective daydreaming can be painfully revealing of one’s fears while simultaneously stirring life-giving visions for relationality and solidarity amid apocalyptic thinking and individualist responses to global crises.